Failure Mode and Effects Analysis of Diesel Engine for Ship Navigation System Improvement - Faturachman, Danny; Shariman, Mustafa; Octaviany, Fanny; Novita, Theresia D. (2013)
Indonesia is the world’s largest archipelago, 2/3 of the country is covered by sea. But due to many factors a lot of ship accidents occurred every year, and claiming a large number of casualties. Efforts have been done to improve the safety of domestic sea transportation, as the result to be fully compliance to the SOLAS (Safety Of Live At Sea) regulations regarding to the IMO (International Maritime Organization) convention, worsen by varying sea and cargo characteristic, and low educated passengers, they are very vulnerable to accidents. There are so many accidents in sea transportation in Indonesia, especially in 2005-2010 is due to human errors and only a few caused by natural factors and others. Most of the accidents occur due to the low awareness of the aspects of security and safety. Equipment’s and system on board ship, will not remain safe or reliable if they are not maintained. Failure Mode and Effects Analysis (FMEA) approach is chosen as a risk assessment methodology in this paper to synthesize the potential failure modes and their associated causes for product design, especially in ship diesel engine. In this paper, the study proposes the fuel oil system in the ship diesel engine. Fuel oil system is extremely important system on a ship which is designed to supply clean fuel oil to main engine, diesel generators and emergency diesel generators. FMEA is an effective tool or technique used for identifying possible failures and mitigating their effects. In various life cycle phase of diesel engine, FMEA activities are executed, and detailed FMEA documents are usually used as reference. Design changes can be executed according to the existing FMEA documents, especially for the most dangerous failure modes with high prevention difficulty.